Effect of adding exogenous acyl homoserine lactone signal to Pseudomonas aeruginosa premature culture and prediction of signal binding domain in Rhamnolipids RhlA enzyme - Masarra M Sakr; Ghadir El-Housseiny; Noha S Elsayed (Ain Shams University, 2022)
The hierarchy of quorum sensing system plays a crucial role in Pseudomonas (P.) aeruginosa virulence and production of important industrial bacterial products like rhamnolipids and proteases. In this study, the effect of adding exogenous acyl homoserine lactone synthetic signal to premature culture of P. aeruginosa on the production of protease and rhamnolipids was investigated. At early exponential phase, induction of rhamnolipid production showed a more rapid response than protease production. Prediction of the 3D structure of the acyl transferase RhlA enzyme, which is the first key enzyme in rhamnolipid synthesis, was then done using I-Tasser program to investigate the possible protein structure that might influence the response to N-acyl-homoserine lactone (AHL) presence. With a good C-score, 3D modelling showed RhlA to have AHL binding pocket where ten ligand binding site residues were elucidated in the protein. Multiple sequence alignment revealed low homology with LuxR proteins. Although conserved residues were depicted from the alignment, they were different from the ligand binding residues suggesting that AHL binds to RhlA with a different mechanism than LuxR proteins. After further bioinformatics analysis, we found that RhlA binds to AHL in a mechanism similar to lactonase enzyme. In conclusion, the in silico domain and protein alignment analysis revealed an AHL binding site in RhlA enzyme protein structure